2022
DOI: 10.1038/s41598-022-07241-0
|View full text |Cite
|
Sign up to set email alerts
|

Salivary S100 calcium-binding protein beta (S100B) and neurofilament light (NfL) after acute exposure to repeated head impacts in collegiate water polo players

Abstract: Blood-based biomarkers of brain injury may be useful for monitoring brain health in athletes at risk for concussions. Two putative biomarkers of sport-related concussion, neurofilament light (NfL), an axonal structural protein, and S100 calcium-binding protein beta (S100B), an astrocyte-derived protein, were measured in saliva, a biofluid which can be sampled in an athletic setting without the risks and burdens associated with blood sampled by venipuncture. Samples were collected from men’s and women’s collegi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Given this overlap in the onset of microbiome changes between this study and previous studies, it is likely that SHIs and mTBIs may take between 48 and 72 hours to lead to changes in gut microbial diversity. Previous works have reported that cognitive deficits such as memory impairment, decreased executive function and response time, as well as increases in peripheral neuroinflammatory markers, including S100 calcium-binding protein beta (S100B) and neurofilament light (NfL) 67,[86][87][88][89] , appear to occur before the shift in microbial diversity others have observed in rodent models of mTBI and that we report here 48 . Thus, a short-term analysis examining fluctuations in peripheral biomarkers of neuroinflammation and cognitive function following SHI and mTBI could determine if the acute changes in the gut microbiome following brain trauma are linked with the severity of cognitive deficits and pro-inflammatory profiles.…”
Section: Discussionsupporting
confidence: 46%
“…Given this overlap in the onset of microbiome changes between this study and previous studies, it is likely that SHIs and mTBIs may take between 48 and 72 hours to lead to changes in gut microbial diversity. Previous works have reported that cognitive deficits such as memory impairment, decreased executive function and response time, as well as increases in peripheral neuroinflammatory markers, including S100 calcium-binding protein beta (S100B) and neurofilament light (NfL) 67,[86][87][88][89] , appear to occur before the shift in microbial diversity others have observed in rodent models of mTBI and that we report here 48 . Thus, a short-term analysis examining fluctuations in peripheral biomarkers of neuroinflammation and cognitive function following SHI and mTBI could determine if the acute changes in the gut microbiome following brain trauma are linked with the severity of cognitive deficits and pro-inflammatory profiles.…”
Section: Discussionsupporting
confidence: 46%
“…However, Monroe et al [ 35 ] failed to demonstrate an association between S100B salivary levels and head impacts exposure while measuring the levels of S100B in the saliva of 65 water polo players before and after a competitive tournament.…”
Section: Salivary Biomarkersmentioning
confidence: 99%
“…There is only one study that investigated the role of salivary NfL in the diagnosis of mild TBI. Monroe et al [ 35 ] reported that salivary NfL was directly associated with head impact frequency and cumulative head impact magnitude in their study on water polo players, concluding that repeated head impacts may cause axonal injury, even in asymptomatic athletes.…”
Section: Salivary Biomarkersmentioning
confidence: 99%
“…However, studies reported that other body fluids can also be used for evaluating the biomarkers and they also have prognostic and monitoring values. For example, salivary S100B has been reported as a biomarker for repeated head injuries causing concussions in water polo athletes and S100B levels are prognostic of repeated head impacts causing axonal injury even in asymptomatic athletes [ 89 ]. However, Hasselblatt et al [ 90 ] reported that increased serum levels in sprinters might originate from extracranial sources and are not associated with brain injury.…”
Section: Type Of Samplementioning
confidence: 99%